2008
DOI: 10.1182/blood-2007-06-094763
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic endothelium shows lactadherin-dependent phagocytosis of aged erythrocytes and apoptotic cells

Abstract: IntroductionCells that are going into apoptosis expose phosphatidylserine (PS) on their surface that serves as an "eat me" signal for both professional phagocytes (such as macrophages, B lymphocytes, and immature dendritic cells) and nonprofessional phagocytes (such as fibroblasts and epithelial cells). 1 Phagocytes recognize apoptotic cells directly via the PS receptor or indirectly via ␣ v -integrins that are present on the phagocyte surface. 2 In the latter process, ␣ v ␤ 3 and ␣ v ␤ 5 integrins recognize P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 36 publications
(35 reference statements)
1
66
0
Order By: Relevance
“…Previously, we showed that endothelial cells are capable of lactadherin-dependent phagocytosis of RGD-modified RBC. 16,20 In the present study we provide evidence for endothelial cell erythrophagocytosis via this pathway by reporting on the interactions between PS-exposing RBC and endothelium in in vitro models mimicking (patho)physiological conditions. We show that, in the presence of lactadherin, PSexposing RBC have severely reduced deformability, and are phagocytosed by endothelial cells under both static and flow conditions.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previously, we showed that endothelial cells are capable of lactadherin-dependent phagocytosis of RGD-modified RBC. 16,20 In the present study we provide evidence for endothelial cell erythrophagocytosis via this pathway by reporting on the interactions between PS-exposing RBC and endothelium in in vitro models mimicking (patho)physiological conditions. We show that, in the presence of lactadherin, PSexposing RBC have severely reduced deformability, and are phagocytosed by endothelial cells under both static and flow conditions.…”
Section: Introductionmentioning
confidence: 96%
“…Clearance and subsequent processing of innate cells should initiate an immunosuppressive effect rather than an immunostimulatory effect, to prevent autoimmune reactions and inflammation. 19 Since endothelial cells, like macrophages, are equipped with all elements of the immunosuppressive PS-lactadherin αv-integrin pathway 16,20 it seems reasonable to assume that under certain circumstances they actively engage this pathway. Previously, we showed that endothelial cells are capable of lactadherin-dependent phagocytosis of RGD-modified RBC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MFGE8 displays three types of functions. First, MFGE8 promotes phagocytosis of apoptotic cells by avb3/b5 integrin-expressing phagocytes (Hanayama et al, 2002), endothelial and epithelial cells (Nandrot et al, 2007;Fens et al, 2008). In Mfge8-deficient mice, impaired elimination of apoptotic cells leads to autoimmune symptoms in old animals (Hanayama et al, 2004), and mammary gland inflammation after repeated pregnancies in females (Atabai et al, 2005;Hanayama and Nagata, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the breast it promotes phagocytosis of apoptotic cells by ανβ3/β5 integrin-expressing phagocytes [20], as well as in endothelial and epithelial cells [21,22]. Prolactin is a potent inducer of MFGE8 expression in macrophages [23].…”
Section: Introductionmentioning
confidence: 99%